Corrosion behaviour of medium entropy alloy deposited on low carbon steel substrate by innovative welding method - Simion, George; Mirza-Rosca, Julia Claudia; Voiculescu, Ionelia; Scutelnicu, Elena (Elsevier BV, 2024)
In recent decades, thanks to the advancements within materials science and engineering, a novel class of metallic compounds, named high and medium-entropy alloys, has begun to capture the attention of researchers world-wide. Despite their excellent mechanical and anticorrosive properties, the widespread usage of these materials in industrial applications still remains a challenge and a subject worthy of investigation. In the present work, an innovative concept of developing high and medium-entropy alloys by deposition welding technique is presented and analysed in detail. Melting a bundle of rods by the Gas Tungsten Arc Welding (GTAW) method, in the same molten pool, a medium-entropy alloy (MEA) from the AlCrFeNi system is deposited on a low carbon steel sub- strate. In order to increase the chemical homogenization of the deposited material and to eliminate or reduce the eventual defects that may occur, electric arc remelting without using filler metal was performed in transverse, longitudinal, or combined (transverse and longitudinal) direction relative to the initial deposition welding direction. The assessment of the resistance to corrosion, modifications of microstructure, chemical composition and hardness have revealed that the medium-entropy alloy, obtained by melting in the same welding pool of several common welding rods with various chemical compositions, is an innovative, sustainable, and advantageous alternative to stainless steel materials.
Keywords: Deposition by GTAW Rods bundle Medium entropy alloy Microstructure Chemical analysis Hardness Corrosion